2006
DOI: 10.1021/nl062513v
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Engineering of a Cellular Interface with Semiconductor Nanoparticle Films for Photoelectric Stimulation of Neurons

Abstract: The remarkable optical and electrical properties of nanostructured materials are considered now as a source for a variety of biomaterials, biosensing, and cell interface applications. In this study, we report the first example of hybrid bionanodevice where absorption of light by thin films of quantum confined semiconductor nanoparticles of HgTe produced by the layer-by-layer assembly stimulate adherent neural cells via a sequence of photochemical and charge-transfer reactions. We also demonstrate an example of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
142
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 55 publications
2
142
0
Order By: Relevance
“…Thus, the measured photocurrent originates from electrons injected from the electrode surface in response to hole accumulation. 149 The authors further suggested resistive coupling as a mechanism of neuronal light stimulation.…”
Section: Qd Nanostructured Interfacementioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the measured photocurrent originates from electrons injected from the electrode surface in response to hole accumulation. 149 The authors further suggested resistive coupling as a mechanism of neuronal light stimulation.…”
Section: Qd Nanostructured Interfacementioning
confidence: 99%
“…147,149 Two routes were demonstrated: antibody-antigen recognition and peptide recognition. 147 The antibody-antigen approach included a primary antibody binding to a specific cell surface receptor.…”
Section: Direct Qd-neuron Interfacementioning
confidence: 99%
See 3 more Smart Citations